Key interindividual determinants in MDMA pharmacodynamics. (1st February 2018) - Papaseit, E.; Torrens, M.; Pérez-Mañá, C.; Muga, R.; Farré, M.
ABSTRACT: Introduction : MDMA, 3, 4-methylenedioxymethamphetamine, is a synthetic phenethylamine derivative with structural and pharmacological similarities to both amphetamines and mescaline. MDMA produces characteristic amphetamine-like actions (euphoria, well-being), increases empathy, and induces pro-social effects that seem to motivate its recreational consumption and provide a basis for its potential therapeutic use. Areas covered : The aim of this review is to present the main interindividual determinants in MDMA pharmacodynamics. The principal sources of pharmacodynamic variability are reviewed, with special emphasis on sex-gender, race-ethnicity, genetic differences, interactions, and MDMA acute toxicity, as well as possible therapeutic use. Expert opinion : Acute MDMA effects are more pronounced in women than they are in men. Very limited data on the relationship between race-ethnicity and MDMA effects are available. MDMA metabolism includes some polymorphic enzymes that can slightly modify plasma concentrations and effects. Although a considerable number of studies exist about the acute effects of MDMA, the small number of subjects in each trial limits evaluation of the different interindividual factors and does not permit a clear conclusion about their influence. These issues should be considered when studying possible MDMA therapeutic use.